KEMITRAAN DALAM SISTEM AGRIBISNIS PISANG MAS (STUDI KASUS KELOMPOK TANI ARJUNA) DI KECAMATAN SUMBERREJO KABUPATEN TANGGAMUS - Renaldi Renaldi; Suriaty Situmorang; Dyah Aring Hepiana Lestari (Lampung University, 2022)
The purpose of this study was to determine the implementation of the partnership pattern in the agribusiness system between PT Great Giant Pineapple and Koperasi Hijau Makmur, Arjuna Farmer Group and banana mas farmers in Tanggamus Regency. The location was determined deliberately, considering that Tanggamus Regency has been the center for the production of golden/mas banana in Lampung Province. The number of respondents in this study was 39 households taken simply randomly. Data collection was conducted in May - August 2020. The analytical methods used were farm income analysis and qualitative descriptive analysis. The results showed that the average income over the total cost of farming bananas mas was IDR 4,494,342 / hectare and an R/C of 1.27. The partnership pattern carried out by PT Great Giant Pineapple with Koperasi Hijau Makmur, Arjuna Farmer Group and mas banana farmers is an agribusiness operational cooperation partnership pattern. The procurement of agricultural production facilities covering the area of land, labor, seeds, fertilizers, pesticides and agricultural tools is in accordance with the exact six applications recommended by the company and the needs of the farmers. Processing of mas bananas includes the stages of weighing, handing, washing, grading, and packing. The marketing channel of mas banana is monopsony and the marketing agencies involved are farmer groups, cooperatives, and PT. Sewu Segar Nusantara, while support services included farmer groups, cooperatives, information and communication technology.Key words: agribusiness system, agricultural, banana mas, partnership.